Diluted Bee Venom Injection Reduces Ipsilateral Mechanical Allodynia in Oxaliplatin-Induced Neuropathic Mice - Yoon, Seo-Yeon; Yeo, Ji-Hee; Han, Seung-Dae; Bong, Dong-Jun; Oh, Beomsoo; Roh, Dae-Hyun (PHARMACEUTICAL SOC JAPAN, 2013)
Oxaliplatin, which is used as one of anti-cancer drugs, commonly induces peripheral neuropathic pain. We have previously reported that an injection of diluted bee venom (DBV) produced a significant anti-nociceptive effects in several pain models of mice or rats. In this study, we evaluated time- and dose-dependent development of oxaliplatin-induced mechanical allodynia in bilateral hind paws of mice, and investigated the effect of DBV injection on this mechanical allodynia. DBV (0.1 mg/kg) was subcutaneously injected into the Zusanli acupoint 2 weeks after oxaliplatin (10 mg/kg) injection. One hour after DBV injection, we observed a significant reduction of mechanical allodynia in the ipsilateral hind paw, but not in the contralateral hind paw to DBV injection site. We subsequently examined whether this effect of DBV was related to the activation of peripheral nerves in DBV injected site, and then whether it was mediated by the activation of spinal cord alpha-2 adrenoceptors or opioid receptors. Subcutaneous pre-injection of 2% lidocaine (40 mg/kg) into the Zusanli acupoint completely blocked the anti-allodynic effect of DBV. Intrathecal pretreatment with yohimbine (25 mu g/mouse), an alpha-2 adrenoceptor antagonist, also prevented the anti-allodynic effect of DBV, whereas pretreatment with naloxone (20 mu g/mouse), an opioid receptor antagonist, did not block the effect of DBV. Taken together, these findings demonstrate that DBV injection into the Zusanli acupoint significantly reduces ipsilateral mechanical allodynia generated by oxaliplatin in mice, and also suggest that this anti-allodynic effect is dependent on the peripheral nerve activation in injected site and spinal cord alpha-2 adrenoceptors.